A COMMENT ON VARIABLE ANNUITIES - Soldofsky, Robert M.; McMahon, Walter W. (Journal of Finance, 1957)
Variable Annuities are the subject of considerable discussion by individuals who identify themselves with life insurance companies and security dealers. The paper by Mr. Albert Linton published in the May, 1956, issue of the Journal of Finance is a case in point. This comment does not attempt to marshall arguments for or against variable annuities, but is concerned only with the major factors determining the size of the payments to be made from a variable annuity fund during the payment period. In Mr. Linton's Table 2, the assumption is made that the variable annuity payment would follow Standard and Poor's index of stock prices.1 The other major factor influencing the size of the annuity payment, the cash dividends that will be received by and added to the annuity fund during the period of the annuity payments, is omitted. This is comparable to omitting interest on the standard annuity contract. The purpose of Table 2 was evidently to display the magnitude of the fluctuations in variable annuity payments in contrast to the absolute dollar stability of the payments made under the terms of a traditional annuity contract. Mr. Linton emphasizes that “irate and disillusioned policyholders” might write letters to insurance commissioners and even congressmen when payments fall under variable annuity contracts. Such pressure might have been (or may be) the opportunity for federal regulation of those life insurance companies that issue variable annuity contracts. Column 1, Table 1, in this comment sets forth the fixed payment of $100 per month specified by Mr. Linton, Column 2 reproduces the assumed monthly payment made under a variable annuity contract as shown by Mr. Linton in his. Table 2, and Column 3 presents a revised statement of the monthly payment under a variable annuity contract taking cognizance of the dividends received by the annuity fund during each year of the life of the annuity. The period 1926 to 1954 is the period selected by Mr. Linton. According to Mr. Linton's presentation, the payments made under the variable annuity were less than those under the traditional contract in twelve of the twenty-nine years. The revised variable annuity payments fall below the fixed monthly payments of $100 in only three years. Furthermore, the lowest payment under the revised computation is $83 per month as compared with $49 per month shown by Mr. Linton. Certainly the intensity of the remarks in the policyholders' letters would be different if the variable annuity payments fell 17 per cent rather than 51 per cent below a norm established by the payment of a fixed number of dollars under a fixed annuity contract. Fixed annuity policyholders may well complain about the opportunities missed when they compare their $100 with the more than $200 monthly income in 1954 that might have been possible under a variable annuity contract. In the computation of Column 3, Table 1, the advantages accruing to the variable annuitant during the accumulation period have been foregone. Mr. Linton recognizes this advantage in suggesting that the rate of growth of funds during the accumulation period invested in a well-selected, properly diversified group of stocks has been larger than the rate of interest achieved by the investment portfolios that are the basis for traditional annuity contracts. We believe that such higher yields on equities are not dependent on inflation given the maintenance of our long-run rate of economic growth and that this relationship is very likely to continue. This position, however, must be left undefended since the space that may be alloted to a comment is very limited. Let the case of the conservative be admitted, however. The holder of a variable annuity contract, the annuitant, would take more risk with respect to the number of dollars he will eventually receive. Life insurance companies, other financial institutions, and even the structure of the capital markets will be affected by any considerable growth in the use of variable annuities. Such changes are certain to follow whether the life insurance companies themselves or some newly developed type of financial institution handles variable valued annuities.